2018
DOI: 10.2196/10031
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Cancer Treatment Information on the Internet: Observational Study

Abstract: BackgroundFinding the correct medical information in a flood of information from the internet is a significant issue for patients with cancer.ObjectiveWe investigated the reliability of the information on cancer treatment methods available on the internet based on an evaluation by medical oncologists, medical students, and cancer survivors.MethodsUsing Google and Yahoo as the search engines, we carried out the information search using 2 keywords, “cancer treatment” and “cancer cure,” and the top 20 information… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…While professional information may be more broad, social media enables people to share their more personal experiences with medications, treatments, and experiences. Unfortunately, this content is unlikely to apply to all readers, and research has identified approximately 20% of cancer-related social media information is not medically or scientifically accurate [ 59 ] and reliability is low [ 60 ]. Accessing reliable information in a timely manner is one of the critical aspects of today’s health care, given the great emphasis on the patient-centered care model.…”
Section: Discussionmentioning
confidence: 99%
“…While professional information may be more broad, social media enables people to share their more personal experiences with medications, treatments, and experiences. Unfortunately, this content is unlikely to apply to all readers, and research has identified approximately 20% of cancer-related social media information is not medically or scientifically accurate [ 59 ] and reliability is low [ 60 ]. Accessing reliable information in a timely manner is one of the critical aspects of today’s health care, given the great emphasis on the patient-centered care model.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitation of professional knowledge, it is difficult for patients to identify the relevant information, and they are prone to be misled by the wrong medical information, which leads to health anxiety; for instance, physical symptoms are misinterpreted as signals of dangerous diseases, and there is a continual worry of being sick [ 75 ]. Ogasawara found that many websites offer harmful information about cancer, and the proportion of these websites is far higher than that of sites that offer reliable information about cancer treatment [ 76 ] which brings “noise” and intensifies the “increasing tendency” of regular medical institutions. If the development of Internet medical care is allowed to develop savagely and irregularly, it may further aggravate the medical burden of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In a semistructured interview on the use of Chinese language internet information on cancer, most of the 20 respondents reported that they encountered internet health information with questionable quality [ 38 ]. An observational study showed that some sites provide harmful information, and the proportion of these sites was much higher than sites providing reliable information on cancer treatment (N=247) [ 39 ]. The studies above hint at the reasons why the use of internet might increase the probability of residents going to high-level medical institutions.…”
Section: Discussionmentioning
confidence: 99%